ISTVÁN KOLONICS (1826-1892) - ORGELBAUMEISTER AUS SZABADKA IN SIEBENBÜRGEN – II. - Erzsébet WINDHAGER-GERÉD (Studia Universitatis Babeş-Bolyai. Musica)
István Kolonics, born in Szabadka (Subotica), moved to Kézdivásárhely (Târgu Secuiesc) in 1855. He eventually became one of the most famous and most assiduous organ builders of the nineteenth century in Transylvania. He built about two hundred new instruments and repaired several. He also instructed numerous assistants. For many years this guaranteed the organs in Hungarian Catholic and Protestant churches to be in working order. This article continues the presentation of his work from the beginning of his career in Transylvania, the specialities on his instruments, the art of organ building and managing.